Implementation of the Exclusive Breastfeeding Program in Pujud Health Center, Rokan Hilir Regency - Samina Rayanti Matondang; Irwan Muryanto; H. Ahmad Hanafi (Institute of Computer Science (IOCS), 2022)
Based on data from the Pujud Health Center, it is known that the achievement of the Exclusive Breastfeeding program in 2021 is 33.2%. This is still far below the target of the Ministry of Health's Strategic Plan (Renstra) which is 60%. This study aims to obtain information on how to implement the Exclusive Breastfeeding Program at the Pujud Health Center in 2021. This research was conducted in Pujud Selatan Village from April to May 2022. This type of research is a qualitative research using case studies. The informant retrieval technique was purposive sampling with a total of 14 informants consisting of 4 people as key informants and 10 people as supporting informants. Collecting data using observation and in-depth interviews and processed using the triangulation method. The results showed that the implementation of the exclusive breastfeeding program had not run optimally. This is due to several factors such as: the absence of policies/regional regulations (Perda) that regulate exclusive breastfeeding, the absence of supporting facilities and infrastructure, and the absence of a budget for exclusive breastfeeding program activities, counseling using the lecture method, the implementation of Breastfeeding Initiation has not been implemented. Dini (IMD), and lack of monitoring and evaluation (MONEV). The conclusion of this study is that the achievement of the Exclusive Breastfeeding program at the Pujud Health Center is still low, judging from the input indicators (policy, infrastructure and budget) that have not been supported, process indicators (extension, IMD implementation, and Monev) implementation that has not been optimal. Suggestions from this research are the need to make a regional policy/regulation, especially in the Rokan Hilir Regency area to support the Exclusive Breastfeeding program